Covid-19 in the UK: policy on children and schools. (31st August 2022) - Gurdasani, Deepti; Pagel, Christina; McKee, Martin; Michie, Susan; Greenhalgh, Trish; Yates, Christopher; Scally, Gabriel; Ziauddeen, Hisham
Abstract : Deepti Gurdasani and colleagues argue UK covid policy did not give children sufficient priority and question the evidence behind government decisions